(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2018)
Study the simulation of human response during the moving on various roads and represent the human body as discrete masses, springs and damper system. Assessment of vibration condition impacts of human in the perspective of the unfavorable safety impact was introduced. Be that as it may, it is important to do the comprehension the impact of vibration to human body to look at their legitimacy and to plan for the future vision. This paper demonstrates the point of interest estimation of human reaction to vibration, and the displaying of the human body for the appraisal of the vibration hazard.The vibration transmissibility from the beginning of the human body amid the introduction to vertical excitation. The modular parameters are resolved with a specific end goal to comprehend the standards normal modes.The model shows that human reaction relying upon vibration condition. The presentation of the present model to vibration stacking is contrasted and the examination information and a practical contract are found. The presentation of human determination demonstrates a geometric depiction of the parameters which influence the unwavering quality of a basic segment subjected to vibration stacking. The control of the investigative model and the recreation examination in the present work demonstrating the distinctive mode shapes, Eigen values/vectors,and the burdens brought about by such vibration stacking that can lead. The model is introduced to manage the human agreeable and to locate a fitting blend between human reaction and vibration condition.